2017
DOI: 10.1590/1806-9061-2016-0423
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Protein in Diet and Sex Ratio on Egg Production, Egg and Hatching Chick Weight, Fertility, Hatchability and Embryonal Mortality in Pheasants (Phasianus Colchicus)

Abstract: KeywordsEmbryonal mortality, hatchability, pheasant, protein levels, sex ratio.Submitted: November/2016 Approved: January/2017 ABSTRACTThis study was performed to investigate the effects of crude protein (CP) in diet and sex ratio on egg production, egg and hatching chick weight and hatchability traits in pheasants (Phasianus Colchicus). In this study, the treatment groups were constructed as 15% CP-5:1; 15% CP-7:1; 18% CP-5:1; 18% CP-7:1 for CP and sex (male:female) ratio respectively. The eggs were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
9
1
Order By: Relevance
“…Mohiti-Asli et al, (2012) found that fertility, hatchability of total and fertile eggs, and embryonic mortality of hen diet with high protein (CP 17.4 %) were higher than those of hen fed diet with low protein (CP 14.5 %). These results are not consistent with those of Ugurlu et al (2017) who found that the highest fertility (88.76%) and hatchability (71.91%) were determined for the 15% crude protein diet. Table (4) showed that blood serum glucose and total protein were decreased by reducing dietary crude protein levels but not significant.…”
Section: Resultscontrasting
confidence: 99%
“…Mohiti-Asli et al, (2012) found that fertility, hatchability of total and fertile eggs, and embryonic mortality of hen diet with high protein (CP 17.4 %) were higher than those of hen fed diet with low protein (CP 14.5 %). These results are not consistent with those of Ugurlu et al (2017) who found that the highest fertility (88.76%) and hatchability (71.91%) were determined for the 15% crude protein diet. Table (4) showed that blood serum glucose and total protein were decreased by reducing dietary crude protein levels but not significant.…”
Section: Resultscontrasting
confidence: 99%
“…Guinea fowl eggs differ from those of other domestic species with regard to their shape and size, being more rounded and more pointed at the lower end (Gilbert, 2013). Guinea fowl eggs appear similar to those of collar pheasants (Figure 1) and have a similar average weight (34.25 g) (Uğurlu et al, 2017), although the pheasant eggs are browner.…”
Section: Discussionmentioning
confidence: 89%
“…Hocking & Bernard (1997) and Graaf et al (2018) reported that broiler breeder males fed 12% CP had higher sperm concentration than those fed on 16% CP diet. Similarly, Uğurlu et al (2017) reported that fertility and hatchability rate of total eggs in pheasants tended to decrease with increasing levels of CP in the diet. In the present study, cocks were fed with the same diet of the hens that had high levels of CP than their requirements (13-14% vs. 18.3-18.7%).…”
Section: Fertility and Hatchability Of Eggsmentioning
confidence: 88%
“…Fertility and hatchability are two major parameters that highly influence the supply of day-old chicks. Many factors of which nutrition, sex ratio, age, egg weight and storage duration are the most important ones could affect fertility and hatchability of eggs (Praes et al 2014;Uğurlu et al 2017). For the hatchability traits, breed has little effect on hatchability of poultry eggs, although light breeds like White Leghorn have been reported to have high fertility and hatchability (King'ori 2011).…”
Section: Fertility and Hatchability Of Eggsmentioning
confidence: 99%